John Dewey’s perspective on experience, technology and learning: a contemporary study (Revista Apotheke, 2025)
This article analyzes the thinking of the American philosopher John Dewey and how his ideas can still influence contemporary education, which is largely permeated by technological artifacts. We suggest interpreting Dewey’s theory of inquiry from a technological perspective. To this end, we adopt a broader view of technology, seen not only as a set of devices, but as any tool, physical or theoretical, built to solve problems. In this sense, we emphasize that meaningful learning will only occur when inserted in contexts of construction and use of these technological artifacts, both physical and theoretical. This is what we call the “technological cycle of learning”. We also argue that this process necessarily involves the search for problem-solving in a context of problematization, investigation and collaboration.
Keywords: John Dewey; Education; Technology; Learning